2015
DOI: 10.3109/1547691x.2015.1046572
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative human and mouse antibody responses against tetanus toxin at clonal level

Abstract: Tetanus is a highly fatal disease caused by tetanus neurotoxin (TeNT) and remains a major threat to human and animal health, despite preventive strategies. TeNT is composed of heavy and light chain linked by a disulfide bond. The antibody response to TeNT is polyclonal and directed to multiple epitopes within both the light and heavy chains, leading to toxin neutralization. This study was undertaken to localize and compare neutralizing epitopes recognized by human and mouse TeNT-specific antibodies at a clonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Numerous reports have described either murine or human TeNT neutralizing antibodies. 8 , 37 Some of the neutralizing antibodies, when used alone, did not completely neutralize TeNT, but only prolonged the survival of the mice, 8 , 15 , 38 unless used in combination or at high doses. 15 , 39 , 40 The tetanus-neutralizing antibodies 4E12, 3A7, and 4C1, which were developed by Li et al, could completely neutralize 10 × LD 50 using 18 μg of antibody (6 μg each) when used in combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous reports have described either murine or human TeNT neutralizing antibodies. 8 , 37 Some of the neutralizing antibodies, when used alone, did not completely neutralize TeNT, but only prolonged the survival of the mice, 8 , 15 , 38 unless used in combination or at high doses. 15 , 39 , 40 The tetanus-neutralizing antibodies 4E12, 3A7, and 4C1, which were developed by Li et al, could completely neutralize 10 × LD 50 using 18 μg of antibody (6 μg each) when used in combination.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 37 Some of the neutralizing antibodies, when used alone, did not completely neutralize TeNT, but only prolonged the survival of the mice, 8 , 15 , 38 unless used in combination or at high doses. 15 , 39 , 40 The tetanus-neutralizing antibodies 4E12, 3A7, and 4C1, which were developed by Li et al, could completely neutralize 10 × LD 50 using 18 μg of antibody (6 μg each) when used in combination. 13 The human monoclonal antibodies 8A7, 17F7, 8D8, and 16E8 could completely neutralize 1 × LD 50 using 37.5 μg of single antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghafari et al [60] suggested that TTFC may be the immunodominant part of the toxin, i.e., that the fragment may elicit the humoral immune response. Moreover, TT neutralizing antibodies were shown to be mainly directed against TTFC in mouse and human models (100% for mouse models and 75% in a human model) [61]. It is important to note that the many neutralizing antibodies described since the 1980s [62][63][64] cannot individually neutralize TT in vivo.…”
Section: Immunological Properties Against Tetanusmentioning
confidence: 99%